Best Answer

Without any given parameters, the x coordinate can be any value.

More answers

The answer depends on the function or observation and without that information the question makes no sense.

Q: What is the x coordinate when the y-coordinate is 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Assuming 6 refers to the value of x, the y coordinate is 1

Because the x coordinate is always followed by the y coordinate as for example the coordinate of (3, 6) is 3 of x horizontally and 6 of y vertically on the Cartesian plane

It is the average of -2 and +6, that is, x = 2

the "x" coordinate is called "x"

Just simply set x equal to 0 in the original equation, and solve for y. Then set y equal to 0 in the original equation and solve for x. When you solve for x, you put that answer for the x coordinate, and a 0 for the y coordinate, and when you solve for y, you put that answer in for the y coordinate, and a 0 for the x coordinate. Let x=0 in y=-6x+9 y=-6(0)+9 y=0+9 y=9 Now put a 9 for your y coordinate, and a 0 for your x coordinate. (0,9). Let y=0. y=-6x+9 0=-6x+9 Subtract 9 on both sides. 0-9=-6x+9-9 -6x=-9 Divide by -6 on each side. (-6x)/-6=-9/-6 x=1.5 Now put a 1.5 for your x coordinate, and a 0 for your y coordinate. (1.5,0). Your final answers are (0,9) and (1.5,0).

Related questions

If two numbers are given, the first one is usually the x-coordinate, the second, the y-coordinate.

Assuming 6 refers to the value of x, the y coordinate is 1

Because the x coordinate is always followed by the y coordinate as for example the coordinate of (3, 6) is 3 of x horizontally and 6 of y vertically on the Cartesian plane

The x-coordinate of the midpoint is the average of the x-coordinates of the two given points. Similar for the y-coordinate.

y = 5x - 4 Substitute 6 in for y; then solve for x: 6 = 5x -4 10 = 5x 2 = x So, the x-coordinate is 2.

It is the average of -2 and +6, that is, x = 2

the "x" coordinate is called "x"

Its x coordinate is 0.The abscissa (x-coordinate) is zero.

your x goes first. for example : 3, 6 3 is your x and 6 is your y

The answer depends on the functional relationship between x and y - if any.

Just simply set x equal to 0 in the original equation, and solve for y. Then set y equal to 0 in the original equation and solve for x. When you solve for x, you put that answer for the x coordinate, and a 0 for the y coordinate, and when you solve for y, you put that answer in for the y coordinate, and a 0 for the x coordinate. Let x=0 in y=-6x+9 y=-6(0)+9 y=0+9 y=9 Now put a 9 for your y coordinate, and a 0 for your x coordinate. (0,9). Let y=0. y=-6x+9 0=-6x+9 Subtract 9 on both sides. 0-9=-6x+9-9 -6x=-9 Divide by -6 on each side. (-6x)/-6=-9/-6 x=1.5 Now put a 1.5 for your x coordinate, and a 0 for your y coordinate. (1.5,0). Your final answers are (0,9) and (1.5,0).

If the coordinates are (3,11) (9,11) (9,6) (3,6) just look at the changes in the first number (the x coordinate) and the changes in the second number (the y coordinate). In this case, the x coordinate changes by 6 and the y coordinate changes by 5. You multiply the two and you have the area, 30. Note: doesn't work if the first number and the second number change in every coordinate